If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 10 = 6x + 12 Reorder the terms: 10 + 2x = 6x + 12 Reorder the terms: 10 + 2x = 12 + 6x Solving 10 + 2x = 12 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 10 + 2x + -6x = 12 + 6x + -6x Combine like terms: 2x + -6x = -4x 10 + -4x = 12 + 6x + -6x Combine like terms: 6x + -6x = 0 10 + -4x = 12 + 0 10 + -4x = 12 Add '-10' to each side of the equation. 10 + -10 + -4x = 12 + -10 Combine like terms: 10 + -10 = 0 0 + -4x = 12 + -10 -4x = 12 + -10 Combine like terms: 12 + -10 = 2 -4x = 2 Divide each side by '-4'. x = -0.5 Simplifying x = -0.5
| 26x-28x=6-8 | | 6x+21y-26x+64y=0 | | (-2x^6y)(x^7y^5)= | | 9.3z-8.3z-7.2=-5.3+8.4 | | y=11(0.75) | | 10p^2-21p+8=0 | | 8w^2-28w-60=0 | | x^4-2x^2=7x-5 | | (a^2)(b)+3b=cforb | | (a^2)(b)+3b=cforb | | -33+21=-2x+5x | | 2x+4+50=90 | | 100-5x=50 | | 3-2x=-2x+1 | | 4j-2j+10=j | | 8xn+4=80 | | 6x-2+3x=61 | | 13x+4y=5.88 | | -7=3x+4 | | 48=15x-3x | | 3(n+5)=6-3(n-7) | | -3x+5y-7=0 | | 8(1.5+.5y)-4y=12 | | 5-2(x+5)=40 | | 4x(126)= | | 20-5s=8 | | x^2(x-3)(x^2-9)(x^2+4)=0 | | W=Fa+FB | | 6x^2(36)= | | x^2+18x+y^2=-17 | | (4x+3)-5=5(x+4) | | x*12+-42+85=246 |